Design, formulation, and physicochemical evaluation of periodontal propolis mucoadhesive gel - Abolfazl Aslani; Negar Malekpour (Wolters Kluwer Medknow Publications, 2016)
Background: Periodontitis is a disease of tooth supporting tissues, and Gram-negative Bacteria are the main cause of this. Propolis has antibacterial, anti-inflammatory, and antioxidant effects due to its high polyphenol and flavonoids content. The aim of this study is the formulation of a mucoadhesive gel containing concentrated extract of propolis for treatment of periodontitis. Materials and Methods: Formulations containing carbopol 940, sodium carboxymethylcellulose (NaCMC), hydroxypropyl methylcellulose K4M, and propolis extract were prepared. Among ten prepared formulations, five formulations had acceptable and proper physical appearance and uniformity; thus, they were selected for physicochemical tests (centrifugal, thermal change, cooling and heating, freeze and thaw, thermal stress, and pH evaluation), quantification of flavonoids, viscosity, mucoadhesion, drug release, and syringeability tests. We investigated the antibacterial activity of F10 (carbopol 940 1%, NaCMC 3%) against Porphyromonas gingivalis using the disk diffusion method. Results: Phenolic content was measured 39.02 ± 3.24 mg/g of concentrated extract as gallic acid and flavonoid content was determined 743.28 ± 12.1 mg/g of concentrated extract as quercetin. Highest viscosity (3700 cps) and mucoadhesion (21 MPa) were seen in F10. Study of release profile in F10also revealed that propolis could release from this system in more than 7 days. All of the five selected formulations had ease of syringeability in 21-gauge needle for drug delivery into periodontal pocket. In the disk diffusion method, F10produced significant growth inhibition zones against P. gingivalis. Conclusion: Controlled release of drug into periodontal pocket helps effective treatment and recovery, higher persistence and reduces drug use frequency. Increase of carbopol 940 leads to viscosity and mucoadhesion elevation and accordingly decreases of release rate.F10was the best formulation because of highest viscosity and mucoadhesion and lowest release rate. It had efficient function in treatment of periodontitis, so we recommend it for clinical evaluation.